Allium cepa L. as a natural antioxidant: Its efficacy in combating heat stress-induced physiological alterations - Ayobami O. Sobanke; Afusat Aiyeola; Frances I. Okwuonu; Wuraola S. Nnaemeka; Jeremiah C. Ndubuisi; Franklin I. Udeoji; Jane N. Adiele (Human Nutrition & Metabolism)
Heat stress (HS) is a major physiological stressor that induces oxidative damage, inflammation, and metabolic disruptions, all of which cause harm to health. This study investigates the potential protective effects of Allium cepa L. (AC), against the physiological alterations brought on by HS. Twenty male rats were utilized in this study and divided into 4 groups: Control, HS, AC, and HS + AC. Rats were exposed to 38–39 °C for 2 h each day for three weeks to induce HS while 1.0 ml/100 g body weight of ethanolic extract of AC was administered orally for three weeks. Hematological parameters, inflammatory markers, and lipid profiles were analyzed using blood samples obtained through heart puncture.The findings demonstrated that HS significantly lowered levels of hemoglobin (HB), red blood cell (RBC) counts, and antioxidant enzyme activity. However, there was a significant rise in the levels of inflammatory markers, platelet counts, LDL-c triglyceride (TG), total cholesterol (TC), and white blood cell (WBC). Many of these alterations were reversed by AC supplementation, by increasing RBC counts, HB levels, and antioxidant enzyme activities while decreasing LDL-c, TG and TC, MDA, and TNF-α (tumor necrosis factor-α). However, the positive benefits of AC were partially diminished in the HS + AC group, perhaps due to the severe oxidative stress caused by heat stress (HS).This study highlights the probable potential of AC as a natural antioxidant in modifying heat stress-induced oxidative damage, hematological changes, and lipid metabolism disruptions; however, its protective effects are insufficient to mitigate heat stress. Therefore, further research is required to explore the other possible underlying mechanisms.